2016
DOI: 10.1071/an15613
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effect of sheep urine patch size and nitrogen loading rate on cumulative N2O emissions

Abstract: Abstract. Ruminant urine nitrogen (N) concentration and volume are important parameters influencing the size and N loading rate of urine patches deposited to soil. Such parameters can influence N cycling and emissions of the greenhouse gas, nitrous oxide (N 2 O) from grazed grassland, yet, there is limited information on the effect of these parameters within typical ranges reported for sheep. We used an automated, high-frequency gas monitoring system to investigate N 2 O emissions from varying urine N applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Hence, dung deposition has a significant effect on the chemical status of the soil and thus presents a potential source of available nutrients for plants [ 56 , 57 ]. Furthermore, urine is another source of nutrient especially N, which occurs primarily as a hydrolyzed urea, and is easily plant-available after deposition [ 58 ] and enables increased plant biomass N uptake and biomass productivity [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, dung deposition has a significant effect on the chemical status of the soil and thus presents a potential source of available nutrients for plants [ 56 , 57 ]. Furthermore, urine is another source of nutrient especially N, which occurs primarily as a hydrolyzed urea, and is easily plant-available after deposition [ 58 ] and enables increased plant biomass N uptake and biomass productivity [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recognise that urine and dung patches are not normally this large, and have “edges”, but this method of application was deemed the most appropriate to simulate the urine patch and dung pat. It is possible that by applying the N source across the whole area of the chamber that N 2 O production and emission may have been affected, but there is no evidence to suggest that this would result in either an under- or over-estimate of the true emission ( Marsden et al, 2016 ). In addition to the urine and dung patches that were established for the N 2 O chamber measurements, larger areas of grassland (2 m × 2 m) on each plot (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This position is strongly in agreement with a recent life cycle assessment (LCA) study at the study site (the NWFP), which found that amongst all sources of uncertainty surrounding carbon footprints of grazing enterprises, uncertainty associated with N 2 O EFs is the largest, and therefore hedging the risk through a mixed strategy would be a sensible approach ( Takahashi et al, 2019 ). In this context, other on-farm options that could contribute to the solution package include: light interception control through manipulation of sward structure ( Congio et al, 2019 ); fertiliser selection to enhance pasture growth and thus the stocking rate ( Louro et al, 2016 ); diet formulation to control N load and urination volume ( Marsden et al, 2016 ); and direct control of grazing intensity ( Tang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%